Compositional undulation induced strain hardening and delocalization in multi-principal element alloys. (1st March 2023) - Zhu, Jiaqi; Sun, Ligang; Li, Dongfeng; Zhu, Linli; He, Xiaoqiao
Highlights: Compositional undulation promotes strength-plasticity synergy and strain hardening. Enhanced dislocation multiplication induced by compositional undulation. Compositional undulation induced hcp microbands facilitates strain delocalization. Alternation of hard and soft regions promotes strain hardening and delocalization. Abstract: Multi-principal element alloys (MPEAs) exhibit outstanding mechanical properties due to their unconventional compositions and chemical structures. Rational design of element distribution in such alloys promises for achieving an unprecedented combination of superior properties. Here, using hybrid molecular dynamics and Monte-Carlo simulation method, atomistic models with compositional periodicity and chemical short-range order (SRO) are designed to investigate the effect of compositional undulation on the tensile behavior of CoCrNi medium-entropy alloy (MEA). Specifically, the differences between MEAs with and without compositional undulation in the evolution of defects, local stress-strain state, dislocation nucleation, slip, and its interaction with planar defects are explored. The results reveal that compositional undulation in MEAs can improve the elastic limit and achieve a strong lattice distortion effect which can enhance the dislocation glide resistance. In addition, obvious strain hardening and stress/strain delocalization are observed in the MEA with compositional periodicity, which promotes strength-plasticity synergy. More interestingly, there are formation of many hcp microbands consists of stacking faults, hcp-like structures and nanotwins owing to the compositional undulation. Such structures induced delocalized activation of slip systems which improves the strength/plasticity and strain hardening ability. The proposed compositional design can further optimize the comprehensive mechanical properties in addition to SRO, which provides a feasible approach to design novel MPEAs with exceptional performance. Graphical abstract: Image, graphical abstract